Litter dynamics in post-fire successional forests of Quercus ilex - FERRAN, A.; Vallejo, V. R. (Plant Ecology, 1992)
Forest floor regeneration after fire in a holm oak forest was studied in a chronosequence in Catalonia (NE Spain). The sampled area represented situations of high fire disturbance because of the frequency of wildfires and the high impact of erosive processes. Forest floor bulk samples from the L, F and H layers were taken in 5 burned plots, aging from 0 to 35 years. They were analyzed for dry standing weight, and organic carbon and N content. Plant cover reached almost 100°o two years after the fire. During the first 20 years, shrubs and herbs had the highest surface covering, and thereafter, holm oaks became dominant. Holm oak litterfall stabilized by the fourth year after burning. The major shrub species which were present in the chronosequence had two different patterns with respect to nitrogen: 1) a low litter C/N ratio (i.e. nitrogen fixing species); 2) a high litter C/N ratio. The litter decay coefficients were relatively high, allowing for a rapid structuration and formation of the L and F layers after the fire. Indeed, 95 ° o of the maximum steady standing weight accumulates in 8-9 years. The pattern of cover in the different strata influenced the lateral distribution and variable accumulation of the forest floor layers and determined different turnover rates.
Keywords: C/N ratio; Decay coefficient; Holm oak; mediterranean forest; plant regeneration